A decision support framework for the design and operation of sustainable urban farming systems. (20th September 2020) - Li, Lanyu; Li, Xian; Chong, Clive; Wang, Chi-Hwa; Wang, Xiaonan
Abstract: The increasing population and continuous urbanization make food security prominent in sustainable development. It is important to develop economic and resource-efficient farming solutions to meet food demand. Renewable energy and waste valorization may bring benefits to build sustainable food production systems and facilitate circular economy. This work aims to develop a decision support framework for the stakeholders to quantitatively assess and optimize their urban farming systems for efficient investment and operation. The proposed framework is based on a holistic system model that considers the energy and material consumption in vegetable production processes and the economic and environmental performance of urban farming systems. In the multi-dimensional assessment model, the net present value and cradle-to-gate CO2 emission, water consumption, and land occupation of different configurations of urban farming systems were assessed. In a further development, the assessment model was embedded in an optimization framework to identify the optimal system design and operation. The optimal crop mix and the corresponding cultivation set points (such as temperature, humidity, irradiance, illumination time, and CO2 concentration) for the farming modules were determined via optimization. To demonstrate the proposed framework, a case study on the design and operation of a vertical farm in Singapore was carried out. The case study examined alternative farming systems with glass-enclosed vs window-free structural design, grid vs solar photovoltaic (PV) energy supply, and traditional chemical fertilizers vs food waste compost fertilization. Results showed that plant-factory farming systems integrated with solar PV and beer-residue-derived fertilizer could be a promising and sustainable farming solution for Singapore as a tropical megacity. Graphical abstract: Image 1 Highlights: A framework is developed for the design and operation of urban farming systems (UFS). UFS are analyzed economically and environmentally via modeling, LCA and optimization. The optimum crops and operating conditions for a case study in Singapore are found. Plant factories are more energy efficient than glass greenhouses in tropical weather. Solar PV and waste-to-fertilizer are economic and sustainable means to run UFS.